Recommendations For Web-Based System Analysis Using Hybrid On The Website Hydroponic - Sari T Y; Puspa A K (Bandar Lampung University (UBL), 2017)
hydroponic cultivation technique has been widely used by farmers in Indonesia, especially for growing vegetables. Cultivation of plants hydroponically has several advantages such as: (1) does not require a large area and treatment more practical and thus require less labor, (2) to use fertilizers more efficiently, (3) the plant grow more rapidly and success is assured, (4) planting can be done continuously without depending on the season, (5) can be scheduled so that harvesting can produce crops continuously, and (6) the selling price is more expensive hydroponic vegetables (Lingga, 2005). Hydroponics is the cultivation of plants using water as raw material to support the growth of these plants. For a plant good growth hence the need for adequate nutrition needs. The nutrients can be mixed into the water so that the spread of nutrients to be evenly distributed and easily for dissolved. In addition to nutritional factors that can affect the growth of the well can also be affected by the EC (Electro Conductifity), pH, and temperature environment. All three of these factors can be detected by the sensor, the sensor is controlled by a microcontroller Arduino Uno. Microcontroller function to input signals from the sensors enter the EC, pH, and temperature and then the microcontroller to process the input to generate output results. In the hydroponic system has a model in the planting system that is one which will focus on the study authors used a model NFT (Nutrient Film Technique). NFT (Nutrient Film Technique) is a model of hydroponic cultivation with plant roots lay in a shallow layer of water. To be circulated water and nutrients needed by plants. Rooting can thrive in the nutrient solution. Because there rooting around the layer of nutrient solution, then the system is known by the name of the movie nutrient technique (NFT) (Lingga, 2011). Planting hydroponics has aspects that must be considered such as the type of plant, ambient temperature, ph, nutrients that are suitable for use and EC (Electro Conductifity)these aspects should be in accordance with the plant whatever, which is suitable to be planted simultaneously when viewed from the EC, pH, temperature , Hence the need for recommendation systems